Respuesta :
g(x) = –2x2 + 3x – 5
input = –2, g(-2) = –2(-2)^2 + 3(-2) – 5 = -8 - 6 - 5 = -19
input = 0, g(0) = –2(0)^2 + 3(0) – 5 = -5
input = 3, g(3) = –2(3)^2 + 3(3) – 5 = -18 + 9 - 5 = -14
input = –2, g(-2) = –2(-2)^2 + 3(-2) – 5 = -8 - 6 - 5 = -19
input = 0, g(0) = –2(0)^2 + 3(0) – 5 = -5
input = 3, g(3) = –2(3)^2 + 3(3) – 5 = -18 + 9 - 5 = -14
The value for the input values -2, 0 and 3 are -19, -11 and - 14
Functions and expressions
Given the function g(x) = –2x^2 + 3x – 5
Given the input value of -2, hence;
g(-2) = -2(-2)^2 + 3(-2) - 5
g(-2) = -2(4) - 6 - 5
g(-2) = -8 - 11
g(-2) = -19
Given the input value of 0, hence;
g(0) = -2(0)^2 + 3(-2) - 5
g(0) = -2(0) - 6 - 5
g(0) = - 11
Given the input value of 3, hence;
g(3) = -2(3)^2 + 3(3) - 5
g(3) = -2(9) +9 - 5
g(3) = -18 + 4
g(3) = -14
Learn more on function here: https://brainly.com/question/10439235